2022
DOI: 10.46827/ejfl.v6i4.4575
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation Into Quang Tri Primary School English Language Teacher’s Perspective of Ict Integration During the Covid-19 Pandemic

Abstract: With the transition from face-to-face classes to online classes during Covid-19 epidemic, teachers in Quang Tri have no choice but to integrate ICT into their teaching. At this time ICT has become the most essential tool in educational settings and the subject of many researchers. This study aims to investigate how English teachers perceived ICT integration in terms of the benefits, difficulties as well as challenges of incorporating ICT. The study adopted both quantitative and qualitative methods of data coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…These discoveries align with those outlined in a recent study conducted by Le et al (2022), who found over half of the 70 primary school English teachers agree that technology helps them manage their classrooms and design activities that capture children's attention in virtual classrooms. Likewise, Suleiman and other researchers (2022) highlighted the benefits of virtual classrooms, including student-centered approaches, increased diversity and creativity, accommodation of various learning styles, and greater student participation in lessons.…”
Section: Classroom Management and Engagement In Virtual Classroomssupporting
confidence: 84%
See 2 more Smart Citations
“…These discoveries align with those outlined in a recent study conducted by Le et al (2022), who found over half of the 70 primary school English teachers agree that technology helps them manage their classrooms and design activities that capture children's attention in virtual classrooms. Likewise, Suleiman and other researchers (2022) highlighted the benefits of virtual classrooms, including student-centered approaches, increased diversity and creativity, accommodation of various learning styles, and greater student participation in lessons.…”
Section: Classroom Management and Engagement In Virtual Classroomssupporting
confidence: 84%
“…Teachers with higher digital skills can navigate online resources efficiently, enhance their teaching effectiveness, and select better-quality courses. Also, the findings in this study support the argument that technology can help teachers create high-quality teaching materials, increase their ICT competencies, and improve the teaching process, which has been proven by Le et al (2022), who affirmed that the use of technology in online classrooms can enhance teacher participation and efficiency, particularly for primary school students in complex epidemic situations, and in Elfeky and Elbyaly (2023), who supported the impact of online classrooms on enhancing teachers' digital competencies. This table shows that participants were able to manage and engage children in virtual classrooms, except for item 14.…”
Section: Developing Digital Skills Through Virtual Classroomssupporting
confidence: 79%
See 1 more Smart Citation